Principal Strategies in School Management at the State Vocational High School - Rohmadiyah, Bulan; Zamroni, M Afif; Ismawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to describe the principal's management in implementing education management in vocational high schools. This article uses case study research with data collection from observation interviews and documentation. The informants consist of the principal, vice principal, teachers, staff, and some school members. The findings of this study are Program implementation at SMK Negeri 1 Dlanggu has a prominent position compared to other elements of the education management standard. Each program is implemented by each school community with a high level of awareness and with a predetermined division of tasks. Monitoring and evaluation are carried out based on the education management standards that have been set. School leadership at SMK Negeri 1 Dlanggu follows the education management standard. This can be seen from the hierarchical structure consisting of the Principal, Vice Principal, and Affairs Coordinator. Each member of the leadership team is aware of their respective roles and responsibilities, and they work collaboratively to improve overall school management, with the ultimate goal of achieving educational excellence. The development of the management information system shows relatively good results, although there is still room for further improvement in the utilization of resources to facilitate school administration and management.